Evaluation of sugars, phenolics, carotenoids and antioxidant activities in 22 saudi arabian date cultivars - RAGAB A EL-MERGAWI, (International Journal of Pharma and Bio Sciences, 2017)
Saudi Arabia consumes a significant quantity of date fruits through traditional diets. However, information about the glucose, fructose and sucrose contents in most Saudi Arabia date cultivars at different maturity stages, especially the stage at which date consumed has not been completely reported previously. Therefore, fresh fruits of 22 Saudi Arabian date cultivars were evaluated for their sugars, phenolics, carotenoids and antioxidant activities. Most of tested date cultivars contained high amounts of glucose and fructose whereas sucrose was either not detected or present in low concentrations. Glucose and fructose comprised between 26.6%-43.1% and 25.9% -39.5% of fresh fruits, respectively. Glucose constituted more than 40% of sugars existed Mabroom, Shbibi, Anbra, Um-elkashab, Um-elhamam, Barhi, Nabot Soltan, and Khalas fruits. The glucose/fructose ratios of all tested cultivars were presented in the range 1.02-1.27. Higher concentrations of sucrose were detected in the Qurawia (49.4%) and Nabtat Manea (13.3%). Total sugars content varied greatly among tested cultivars (64.4% and 80.8%) and the highest concentrations were recorded in Khalas (80.8%), Mabroom (80.3%) and Shbibi (80.1%). Total phenolic content was found in the range of 215 to 514 mg gallic acid/100g, and fruits of Nabtat Manea and Metwah contain the highest concentrations (514 and 479 mg gallic acid/100g, respectively). Total carotenoids content of tested date cultivars ranged from 2.0 to 5.46 mg/kg. The antioxidant activities varied between tested cultivars, it ranged between 1.93-14.73 µmol Trolox/g (DPPH method) and 8.28-20.19 µmol Trolox/g (FRAP method). The highest value of antioxidant activity was recorded for Nabtat Manea, while Khalas and Anbra cultivars had the lowest values.